Transition between Mechanisms of Laser-Induced Field-Free Molecular Orientation - Znakovskaya, I.; Spanner, M.; De, S.; Li, H.; Ray, D.; Corkum, P.; Litvinyuk, I. V.; Cocke, C. L.; Kling, M. F. (My University, 2014)
The transition between two distinct mechanisms for the laser-induced field-free orientation of CO molecules is observed via measurements of orientation revival times and subsequent comparison to theoretical calculations. In the first mechanism, which we find responsible for the orientation of CO up to peak intensities of 8×1013 W/cm2, the molecules are impulsively oriented through the hyperpolarizability interaction. At higher intensities, asymmetric depletion through orientation-selective ionization is the dominant orienting mechanism. In addition to the clear identification of the two regimes of orientation, we propose that careful measurements of the onset of the orientation depletion mechanism as a function of the laser intensity will provide a relatively simple route to calibrating absolute rates of nonperturbative strong-field molecular ionization.